Small business financing: survey evidence in West Texas - Wei He; H. Kent Baker (The Journal of Entrepreneurial Finance and Business Ventures, 2007)
We investigate the financial sources of small firms through a survey of sample firms from West Texas. Evidence shows that the two most common start-up financing alternatives are personal savings and commercial bank loans. Commercial banks remain the most popular source of financing for present and future needs, followed by leasing companies and credit unions. Informal types of financing such as business credit cards, and trade credit are used in addition to lines of credit for transaction and working capital purposes. Firms typically review their financial performance monthly and use common cash balances as the primary financial tool.
Keywords: 650